Multi-site clinical assessment of Complete Revitalens MPDS in 2981 contact lens wearers across Europe and USA - González-Méijome, José Manuel (2013)
(MPDS), Complete Revitalens (RevitaLens OcuTec in the US Market), for soft contact lens care in a large “real practice” setting. Method: This is an international multi-center, open-label assessment carried out in 10 countries across Europe and in the USA. Up to 10 subjects who were currently wearing soft contact lenses for at least 1 year and using a MPS as a lens care system were included at each investigational site. Results: Data were collected from 996 European and 1985 American wearers, 75% of those patients wore silicone hydrogel contact lenses. Approximately 94% found the new MPDS “somewhat more effective” to “much more effective” in keeping contact lenses feeling clean and 88% found the new MPDS to be somewhat more effective to much more effective in keeping their lenses feeling comfortable in the evening. Over 93% reported an improvement in vision clearness in the evening after approximately 1 month while using the new MPDS. Wearers with grade 2, 3 or 4 of severity decreased by 11.3, 6.4 and 9.8% over 1 month period for redness, burning and irritation, respectively. After approximately 1 month 83% of wearers declared that they would prefer to use the new MPDS. Conclusions: Over 88% felt their lenses were somewhat to much more comfortable at the end-of-day and 94% found the new MPDS to be somewhat to much more effective in keeping their lenses feeling clean compared to their previous care system.